The use of code-mixing in Indian billboard advertising - Kathpalia, Sujata S. (2015)
One major area of interest in the study of contemporary linguistic landscapes worldwide is the interaction of English with local languages in public spaces. One such example of this is the use of ‘Hinglish’ in Indian media, particularly in Indian advertising. Although some researchers have previously investigated Hindi-English code-switching in Bollywood films as well as print advertisements, relatively little research has been done on the interplay of these two languages on billboards. This current study aims to analyze this aspect of Hindi-English code-mixing involving literary devices in the ‘Amul butter’ advertising campaign which uses billboards to advertise its product throughout India.